CKMT2 functions as a novel oncogenic gene in osteosarcoma, revealed by bioinformatics and experimental approaches - Wu, Xuefei; Ding, Fei; Wu, Weijie; Dong, Honghua (Translational Cancer Research, 2026)
Background: Osteosarcoma (OS) is the most common primary bone malignancy in adolescents, but its pathogenesis remains poorly understood. Creatine kinase mitochondrial 2 (CKMT2) has been associated with tumor progression and prognosis in several cancers. This study aimed to elucidate the role and underlying mechanisms of CKMT2 in OS.Methods: Bioinformatics analyses were conducted using Gene Expression Omnibus (GEO) and Therapeutically Applicable Research to Generate Effective Treatments (TARGET) databases. Western blotting evaluated CKMT2 expression in OS cell lines. Cox regression analyses determined its prognostic significance. Functional assays including Cell Counting Kit-8 (CCK-8), flow cytometry, 5-ethynyl-2'-deoxyuridine (EdU), wound-healing, and Transwell were performed in CKMT2-silenced MG63 cells. Gene Set Enrichment Analysis (GSEA) identified relevant pathways. Potential interacting genes, chemical compounds targeting CKMT2, and its relationship with immune cell infiltration were also investigated.Results: CKMT2 was significantly overexpressed in OS tissues and associated with poor patient prognosis. It was confirmed as an independent prognostic factor. A predictive nomogram integrating CKMT2 with clinical features was developed. CKMT2 knockdown inhibited OS cell proliferation, migration, and invasion. GSEA revealed enrichment in metabolic pathways, especially pyruvate metabolism. Silencing CKMT2 reduced PKM2 and LDHA protein levels, along with pyruvate and lactate content. CKMT2 expression also showed a positive correlation with immune cell infiltration, notably resting mast cells (MCs).Conclusions: CKMT2 serves as a promising prognostic biomarker and potential therapeutic target in OS. It promotes malignant phenotypes by regulating metabolic pathways and influencing the tumor immune microenvironment.